Population pharmacokinetics and individualized dosing of tigecycline for critically ill patients: a prospective study with intensive sampling - Su, Wei; Song, Shuping; Liu, Jieqiong; Yu, Haitao; Feng, Binbin; Wu, Yinshan; Guo, Feng; Yu, Zhenwei (Frontiers in Pharmacology, 2024)
Background: Due to the heterogeneity of critically ill patients, the pharmacokinetics of tigecycline are unclear, and the optimal dosing strategy is controversial.: A single-center prospective clinical study that included critically ill patients who received tigecycline was performed. Blood samples were intensively sampled (8 samples each), and plasma drug concentrations were determined. A population pharmacokinetic (PPK) model was developed and evaluated by goodness-of-fit plots, bootstrap analysis and visual predictive checks. Monte Carlo simulation was conducted to optimize the dosage regimen. Results: Overall, 751 observations from 98 patients were included. The final PPK model was a two-compartment model incorporating covariates of creatinine clearance on clearance (CL), body weight on both central and peripheral volumes of distribution (V1 and V2), γ-glutamyl transferase and total bilirubin on intercompartment clearance (Q), and albumin on V2. The typical values of CL, Q, V1 and V2 were 3.09 L/h, 39.7L/h, 32.1 L and 113 L, respectively. A dosage regimen of 50 mg/12 h was suitable for complicated intra-abdominal infections, but 100 mg/12 h was needed for communityacquired pneumonia, skin and skin structure infections and infections caused by lesssusceptive bacteria.The Tigecycline PPK model was successfully developed and validated.Individualized dosing of tigecycline could be beneficial for critically ill patients.